Entwicklung der Konjunkturforschung im frühen 20. Jahrhundert. Studien zur Entwicklung der ökonomischen Theorie XL - Peter Spahn (Duncker & Humblot, 2022)
»The Formation of Business Cycle Research in the Early 20th Century«: The formation of research on macroeconomic fluctuations in the early 20th century was characterised by a debate on key questions: is the business cycle a problem of applied economic theory, or does it require a fundamentally new synthesis of micro- and macroeconomics? What was the role of money in completing this task? Can macro fluctuations be explained by a collection and inspection of data, or can these data only be properly read by a dominant theory, chosen for analytical reasons?
Keywords: 330; Konjunkturforschung; Wirtschaftsdynamik; Wirtschaftskrise